Managing Systemic Innovation Programs: The Case of Additive Manufacturing - Martinsuo, Miia (Sage Publications Ltd., 2025)
Systemic innovations pursue renewal in a system and complementary systems and require the involvement of multiple organizations. In technology-based systemic innovations, disconnects between subsystems and stakeholders, haphazard innovation timing, and contextual dependency may hinder the progress of such innovations, demanding more coordinated management. This article proposes the concept of a systemic innovation program to be used for creating and implementing complex solutions through multiple parallel and sequential projects in interorganizational cooperation. The case of additive manufacturing reveals requirements to managing systemic innovation programs. Neutral orchestration, mission shaping, project roadmapping, and interorganizational multiproject coordination represent potential key mechanisms for managing systemic innovation programs.